Dual functions of silibinin in attenuating aortic dissection via regulating iron homeostasis and endoplasmic reticulum stress against ferroptosis - Zhen Qi; Qiu-Guo Wang; Meng-Xi Huang; Yi-Fan Zeng; Jing-Yu Li; Zhi-Cheng Duan; Ling Tan; Hao Tang (Cell Death and Disease)
Abstract Aortic dissection (AD) poses a significant threat to cardiovascular health globally, yet its underlying mechanisms remain elusive. Smooth muscle cells death and phenotypic switching are critically important pathological processes in AD. Currently, no pharmacological therapies have proven effective in managing AD. This study aims to elucidate the involvement of ferroptosis in AD progression and explore ferroptosis inhibition as a potential therapeutic approach for AD management. Elevated expression of ferroptosis markers (HMOX1, ACSL4, and 4-HNE) was observed in AD patients and β-Aminopropionitrile (BAPN)-induced mice. In vivo administration of silibinin (SIL) attenuated aortic dilation, inflammation, mitochondrial injury, and ferroptosis. SIL treatment enhanced cell viability and mitochondrial function while reducing reactive oxygen species (ROS) generation and mitigating ferroptosis in primary human aortic smooth muscle cells (HASMCs) induced by RSL3 or IKE. Mechanistically, RNA-sequencing analysis identified dysregulation of iron homeostasis and endoplasmic reticulum stress, which were modulated by SIL. Molecular docking, cellular thermal shift assay, drug affinity responsive target stability, and surface plasmon resonance analysis confirmed HMOX1 as a direct target of SIL, highlighting its role in modulating iron homeostasis. Moreover, NCT-502, a PHGDH inhibitor, reversed the protective effect of SIL in RSL3-induced HASMCs. Conversely, 4-PBA and ZnPP demonstrate a facilitative role. This suggests that SIL plays a crucial role in ferroptosis development by modulating iron homeostasis and endoplasmic reticulum stress-mediated serine biosynthesis, both in vitro and in vivo. Iron homeostasis and endoplasmic reticulum stress of HASMCs drive the development of aortic dissection. These findings unveil a novel role of SIL in mitigating ferroptosis in HASMCs, offering a promising therapeutic avenue for treating AD.